Adsorption and diffusion of lithium on heteroatom-doped monolayer molybdenum disulfide - Sun, Xiaoli; Wang, Zhiguo (Applied surface science, 2018)
[Display omitted] •Adsorption and diffusion of Li on heteroatom-doped MoS2 were investigated.•Doping enhance the adsorption of Li on monolayer MoS2.•Heteroatom-doped monolayer MoS2 can be used as anode materials of LIBs. In this work, heteroatom doping in monolayer MoS2 by substitution of S with nonmetal elements (N, P, As, F, Cl, and I) and substitution of Mo with metal elements (Fe, Co, Ni, Cu, and Zn) was investigated using density functional theory. The adsorption and diffusion of Li on the heteroatom-doped MoS2 monolayer were also studied. Results showed that heteroatom doping can be realized by controlling the synthesis condition, and can enhance the adsorption of Li on monolayer MoS2, especially for p-type doped monolayers. The diffusion energy barriers were slightly decreased as Li diffused towards the doping site, whereas they were increased for the diffusion around the doping site. The maximum values of the diffusion energy barriers were 0.82, 0.62, and 0.72 eV for Ni, Cu, and Cu dopants, respectively, with others around 0.25 eV. The diffusion was not affected by the doping for sites far from the doping position. Thus, heteroatom-doped monolayer MoS2 can be used as an anode material for lithium ion batteries.